Industrial training report: Pejabat Tanah dan Jajahan Kuala Krai / Mohd Lukman Mohd Razali - Mohd Razali, Mohd Lukman (Perpustakaan Tengku Anis, 2018)
Based on the period from 1 August to 31 December I was assigned to go for internship session based on the subject IMC690. I choose the organization of "Pejabat Tanah & Jajahan Kuala Krai "(PTJKK), at the organization I was put under Administration and Financial Department. This report is set out to give the reader full information about my industrial training in "Pejabat Tanah & Jajahan Kuala Krai "(PTJKK). Industrial training is one of the compulsory curriculums in Universiti Teknologi Mara which students need to complete whether in consultant, factory and company. This course is sets up for student in order to give them experience and gain knowledge in working environment before going through the real working life. My industrial training is at "Pejabat Tanah & Jajahan Kuala Krai "(PTJKK) which provide maintenance and construction for land issues. In PTJKK, I have been assigned to administration and financial unit. At this unit, I have been assigned to handle filing whether manual or online, handle mail operation and also as a helpdesk. During my placement, I have learned a lot new knowledge about human resource and financial report. This knowledge is useful for me in future and gives me a lot of advantageous to prepare myself for my future career. Last but not least, in this report included the introduction, brief background about this organisation, task and special project I have been assigned, recommendations and conclusion in details during my industrial training in PTJKK.